Impacts of different coffee systems on soil microbial populations at different altitudes in Villavicencio (Colombia) (2016)
Coffee in Colombia has favorable characteristics for agroforestry practices; farmers traditionally grow coffee under various types of organic coffee systems, mainly dominated by associated systems coffee with shade leguminous tree species, making it one of the essential ecosystems for microorganisms life. This research was developed in the coffee region of Puente Abadia, Villavicencio, Colombia; the objective was to evaluate the heterotrophic aerobic microbial population in Cof fea arabica var. Castilla of bacteria (BP), fungi (FP) and actinomycetes (AP), due to the combined effect of three factors. Factor A was related to two bioclimates zones: Low altitude zone 700 m a.s.l. (Z1) and high altitude zone 700 m a.s.l. (Z2); factor B corresponded to two coffee systems: coffee monoculture system (unshaded) (S1), associated coffee system (shaded) (S2) and control treatment of fruit monoculture system (S3). On the other hand, factor C referred to two sampling depth, corresponding to a 0-20 cm depth (D1) and 20-30 cm depth (D2). Significant differences (P≤0.05) between the Z2*S2*D2 factor interaction caused the highest (BP) and (AP); (AP) also was positively inf luenced by the Z2*S2*D1, Z1*S2*D2 and Z1*S2*D1 interactions (P≤0.05). The (FP) was affected positively by the Z1*S2*D2 and Z1*S2*D1 interactions. The (S2) (shade) had comparative advantages for the soil microbial population, as compared with (S1) and (S3).